Sensitivity and Specificity of Some Laboratory Diagnostic Test in Rheumatoid Arthritis - Basem Rajab; Abdulhamid Alkout; Alaa Lagha; Hadeel Elbouhali (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Rheumatoid Arthritis (RA)is a chronic autoimmune disease affect the joints. It is characterized by a progressive symmetric inflammation occurrence between age 65 to 80 years. Early treatment is confirmed in order to prevent and decrease its complications by different laboratory investigation of immune activation, for example erythrocyte sedimentation rate (ESR) which is a general hematology examination that might indicate and monitor an elevate in inflammatory activity inside the body. The aim of the current study was to evaluate the sensitivity and specificity of some clinical investigation for rheumatic disease to aid early detection and treatment. Methods. A total of 50 elderly individuals were screened in this study and were divided into two categories. The first category collected from departments of Rheumatology in Tripoli University Hospital and Tripoli Central Hospital, and the second category collected randomly from healthy individuals which served as control. Personal information and data relating RA diagnostic tests in patient, including erythrocytes sedimentation rate, rheumatoid factor by latex and Mindray and last test is uric acid. Results. The mean± SD of uric acid between RA cases and control, which was not significant, was 3.96 ± 1.64 and 4.10 ± 2.32 respectively (P=0.7); with AUC was 0.509. While the mean of other results was significant, mean± SD of ESR 62.2 ± 33.3 to 37.5 ± 22.1 (P=0.018); with AUC was 0.694, mean± SD of RF latex was 90.0 ± 187 to 8.08 ± 0.08 (P=0.011); with AUC was 0.709, RA Mindray mean ± SD 73.0 ± 130 to 4.24 ± 5.19 (P=0.006); with AUC is 0.726. Conclusion. The results showed that RF test by latex is good for the diagnosis, with more advantage such as the ease of technique used, fast and low cost.